PKM Pelatihan Figma untuk Meningkatkan Kualitas User Interface Project Mahasiswa Demi Mendukung Hasil Project-Based Learning - Kurnia Prima Putra; Dewi Fatmarani Surianto; Wahyu Hidayat; Jasruddin Jasruddin; Ridwan Daud Mahande (PT. Global Research Collaboration, 2024)
In the era of project-based learning (PjBL), the quality of student learning is a primary concern. However, often the quality of user interface (UI) in these projects is neglected. Therefore, we conducted intensive training using Figma to enhance UI quality in PjBL projects. With a practical approach, students were encouraged to become more engaged and understand UI design concepts better. The results were surprising: there was a significant improvement in the quality of student project UIs. Not only were they more actively involved, but they were also able to apply good design principles. These findings offer new hope in curriculum development and teaching practices for the future, reinforcing Figma's contribution to enhancing student learning quality.